The Impact of Minimum Wage Policies on Energy Efficiency in Indonesia’s Manufacturing Industry - Ega Pratama; Djoni Hartono (Universitas Airlangga, 2026)
Objective: This paper examines whether minimum wage policy affects firms’ energy efficiency, using evidence from Indonesia’s manufacturing sector. It studies how provincial minimum wage increases influence firm-level energy use and addresses a broader economic question of how labor regulation, a non-energy policy, shapes firms’ production behavior and resource allocation in an emerging economy. Design/Methods/Approach: The analysis uses firm-level panel data from large and medium manufacturing establishments in Indonesia for 2017–2019. Provincial economic indicators are matched to firms by location. The empirical strategy combines panel fixed-effects estimation with an instrumental variables approach to address potential endogeneity in minimum wage determination. Findings: Higher minimum wages are associated with lower firm-level energy intensity. The estimated magnitude indicates that a 1% increase in the provincial minimum wage corresponds to a measurable reduction in firms’ energy intensity. The effect is stronger among labor-intensive firms, consistent with firms adjusting production processes and adopting more efficient technologies in response to higher labor costs. Originality/Value: The study links labor market regulation to firm-level production efficiency and energy use. Unlike most research focusing on energy policy, it provides firm-level evidence that minimum wage policy can indirectly influence industrial energy efficiency in an emerging economy. Practical/Policy implications: Minimum wage adjustments may have implications beyond labor market outcomes. The findings suggest that wage-setting institutions can influence firms’ production choices and resource use, with potential efficiency gains arising from cost pressures. This indicates that labor regulation can complement policies aimed at improving industrial efficiency, while highlighting the importance of implementation and compliance mechanisms.